Manufacturing sector development in Sub-Saharan Africa: Does monetary policy matter? - Hope E. Agbonrofo; Ajibola Olusegun (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
This study investigated the effect of monetary policy on the manufacturing sector value added in 24 sub-Saharan African (SSA) countries. The study is motivated by the persistent state of underdevelopment of the manufacturing sector in the region and the palpable dearth of empirical evidence on the sector's response to monetary policy actions as suggested by theory. The study employed panel data from 1995 to 2020 and the framework of the panel ARDL model which is estimated using three dynamic panel estimators - Mean Group (MG), Pooled Mean Group (PMG), and Dynamic Fixed Effect (DFE). Findings from the study showed that the monetary variables are time sensitive and heterogeneous in their effects depending on the long or short-run. We document that while interest rate and the exchange rate had statistically significant negative impacts on manufacturing value added in the long-run only credit to the private sector had no real impact on manufacturing value added in the short and long-run. The implication is that policymakers have to conduct monetary policy in such a manner that mitigates the persistent rise in interest and the depreciation of the domestic currency exchange rates to boost manufacturing value added in the region.
Keywords: E52; N97; O14; 330; Manufacturing value added; monetary policy; panel ARDL; pooled mean group; dynamic fixed effect; SSA